2018
DOI: 10.1080/09670262.2018.1453089
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic variation ofFucusin the eastern Gulf of Bothnia, northern Baltic Sea

Abstract: Fucus vesiculosus and F. radicans (Phaeophyceae) are important habitat-formers on rocky shores in the Bothnian Sea. While both species occur sympatrically along the entire western Bothnian Sea coast, F. radicans has been found only in the northern part of the eastern coast. According to previous studies, the two species can be distinguished based on morphology, F. radicans having narrower thalli and a bushier appearance. However, marine mapping in the eastern Bothnian Sea has revealed that high morphological v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Previous results on spatial genetic structuring of the Baltic Sea F. vesiculosus population have been somewhat mixed. Our work is in line with previous results showing strong structure among spatially closely located populations along the Swedish east coast (Pereyra et al, 2009 ; Tatarenkov et al, 2007 ), the Finnish west coast (Rinne et al, 2018 ), and also at larger scales (Ardehed et al, 2016 ; Johannesson et al, 2011 ). Contrary to this, a wide‐scale study only found significant genetic structuring among local attached F. vesiculosus populations in the Gulfs of Bothnia and Riga, but not among the regions (Pereyra et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous results on spatial genetic structuring of the Baltic Sea F. vesiculosus population have been somewhat mixed. Our work is in line with previous results showing strong structure among spatially closely located populations along the Swedish east coast (Pereyra et al, 2009 ; Tatarenkov et al, 2007 ), the Finnish west coast (Rinne et al, 2018 ), and also at larger scales (Ardehed et al, 2016 ; Johannesson et al, 2011 ). Contrary to this, a wide‐scale study only found significant genetic structuring among local attached F. vesiculosus populations in the Gulfs of Bothnia and Riga, but not among the regions (Pereyra et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Polyploidy has not been found in previous genetic studies of Baltic Sea F. vesiculosus (Ardehed et al, 2016 ; Johannesson et al, 2011 ; Pereyra et al, 2009 ; Rinne et al, 2018 ; Tatarenkov et al, 2005 , 2007 ), but has infrequently been reported elsewhere in Fucus spp. (Coyer, Hoarau, Pearson, et al, 2006 ; Gómez Garreta et al, 2010 ; Sjøtun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Morphology is (within genetic limits) an integrative response of F. vesiculosus to environmental drivers such as irradiance, nutrients, temperature, salinity, and/or hydrology (see Rinne, Björkman, Sjöqvist, Salovius-Laurén, & Mattila, 2018 and citations therein). The frond length, frond width, and stipe width were directly measured in the field for every individual collected in 17 of the 24 stations, covering the overall salinity gradient (see Figure 2).…”
Section: Morphological Traitsmentioning
confidence: 99%
“…F. vesiculosus is widely distributed extending to approximately 3.5 PSU salinity in the north (Bergström and Bergström 1999; Schagerström 2013) and to even lower salinities in the eastern Gulf of Finland (Lehvo and Bäck 2000; Ardehed et al 2016). Fucus radicans, endemic to the Baltic Sea (Pereyra et al 2009), occurs mainly in the Gulf of Bothnia (Johannesson et al 2011; Rinne et al 2018) but also along the west coast of Estonia and in the eastern Gulf of Finland (Pereyra et al 2013; Schagerström 2013; Ardehed et al 2016). The Fucus of the northern Baltic Sea show high genetic and morphological variation both on large and more local scales (Tatarenkov et al 2007; Ardehed et al 2016; Rinne et al 2018), complicating their distinction to two species.…”
Section: Introductionmentioning
confidence: 99%